2019
DOI: 10.1002/adts.201900036
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Atoms Diffusion Mechanism in CuInSe2 Explained by Kinetic Monte Carlo Simulations

Abstract: Adaptive kinetic Monte Carlo simulation (aKMC) is employed to study the dynamics and the diffusion of point defects in the CuInSe 2 lattice. The aKMC results show that lighter alkali atoms can diffuse into the CuInSe 2 grains, whereas the diffusion of heavier alkali atoms is limited to the Cu-poor region of the absorber. The key difference between the diffusion of lighter and heavier alkali elements is the energy barrier of the ion exchange between alkali interstitial atoms and Cu. For lighter alkali atoms lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…On the other hand, recently published Monte Carlo simulations show that for heavy alkali metals (like Rb) the diffusion via V Cu has much lower energy barriers than diffusion via interstitial positions in the lattice, while in case of Na these barriers are comparable [26]. Therefore, it seems likely that Rb preferably occupies Cu sites in Cu-poor material near the GBs or at the surface of the CIGS [26], but is rather unlikely to replace Cu in a stoichiometric CIGS lattice. In samples with a high number of available V Cu , Rb may hence not occupy Na sites at the GBs but directly diffuses into the Cu-poor material at the surface of the CIGS lattice [cf.…”
Section: B Effects On Ffmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recently published Monte Carlo simulations show that for heavy alkali metals (like Rb) the diffusion via V Cu has much lower energy barriers than diffusion via interstitial positions in the lattice, while in case of Na these barriers are comparable [26]. Therefore, it seems likely that Rb preferably occupies Cu sites in Cu-poor material near the GBs or at the surface of the CIGS [26], but is rather unlikely to replace Cu in a stoichiometric CIGS lattice. In samples with a high number of available V Cu , Rb may hence not occupy Na sites at the GBs but directly diffuses into the Cu-poor material at the surface of the CIGS lattice [cf.…”
Section: B Effects On Ffmentioning
confidence: 99%
“…The positive effect of Rb on V OC is-among other mechanisms-generally attributed to the following effects: an Rb-Na exchange mechanism, in which Rb pushes Na into the grain interior leading to improved n CV [15]- [18] as well as a subsequent passivation of the GBs by the Rb itself [19]- [24] leading to improved carrier lifetimes [3], [18], [25]. On the other hand, recently published Monte Carlo simulations show that for heavy alkali metals (like Rb) the diffusion via V Cu has much lower energy barriers than diffusion via interstitial positions in the lattice, while in case of Na these barriers are comparable [26]. Therefore, it seems likely that Rb preferably occupies Cu sites in Cu-poor material near the GBs or at the surface of the CIGS [26], but is rather unlikely to replace Cu in a stoichiometric CIGS lattice.…”
Section: B Effects On Ffmentioning
confidence: 99%
“…[ 19 ] For light alkali metals such as Na and Li, the diffusion via copper vacancies (V Cu ) and the diffusion via interstitial positions in the lattice have comparable energy barriers, thus it was shown that Na can either replace vacant Cu places or occupy interstices in the crystal lattice of CIGSe. [ 25 ] However, for heavy alkali metals, such as rubidium, the energy barrier is much lower for the diffusion via V Cu than for the diffusion via the interstitial positions. [ 25 ] As a consequence, under Cu‐poor conditions, Rb will have a preference to occupy vacant Cu sites, in particular the ones located near the grain boundaries (GBs) or at the surface of the CIGSe absorber, since the large atomic radius of Rb prevents its deeper penetration into the CIGSe grains.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] However, for heavy alkali metals, such as rubidium, the energy barrier is much lower for the diffusion via V Cu than for the diffusion via the interstitial positions. [ 25 ] As a consequence, under Cu‐poor conditions, Rb will have a preference to occupy vacant Cu sites, in particular the ones located near the grain boundaries (GBs) or at the surface of the CIGSe absorber, since the large atomic radius of Rb prevents its deeper penetration into the CIGSe grains. In a stoichiometric CIGSe lattice, it is not probable for Rb to replace Cu due to the low availability of vacancies, and it will remain outside the CIGSe grain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation